A Conservatıve Treatment Approach In A Sceletal Class III Case. A Case Report - Enis Güray; Ali İhya Karaman (Turkish Journal of Orthodontics, 1995)

(untitled)
Rapid maxillary expansion (R.M.E.) has a special place in orthodontic treatments. It is based on the principle of opening of the sutura palatina media. Among indications of the R.M.E. were collaps due to maxillary deficency, nasal insufficiency and cleft palate cases. In this paper, a conservative treatment approach is presented in a sceletal class III case characterized with severe maxillary collaps and nasal obstruction.